2023
DOI: 10.1021/acs.inorgchem.2c04419
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Au/Hydroxide Interface toward Enhanced C–C Coupling for Solar-Driven CO2 Reduction into C2H6

Abstract: The high-grade C2+ products from CO2 photoreduction are limited by the kinetic bottleneck. Herein, a multifunctional Au/hydroxide interface was put forward to improve the C–C coupling. As a prototype, the synthesized Au/ZnSn(OH)6 tuned the CO generation and afforded about 50% electrons toward C2H6 selectivity. The prominent enhancement resulted from the following effects: (1) strong metal–support electronic interactions built an electric field at the interface of ZnSn(OH)6 nearby the Au nanoparticles, leading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…These results suggested that the tuned selectivity from CO to CH 4 was independent of the carrier density on the SrTiO 3 surface, although it indeed presented a positive role for the CH 4 yield. Indeed, similar results were previously demonstrated on Ta 3 N 5 and ZnSn­(OH) 6 . , Insight into the reaction reveals that the difference was that the CO 2 reduction occurred on the {100} facet and Pt 2+ -based cocatalyst for SrTiO 3 and x Pt 2+ -SrTiO 3 , respectively, as confirmed by the TEM and VB-XPS result. Hence, this confirmed that the different CO and CH 4 selectivity for the CO 2 reduction was dependent on the different surface chemistry with the present Pt 2+ species.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…These results suggested that the tuned selectivity from CO to CH 4 was independent of the carrier density on the SrTiO 3 surface, although it indeed presented a positive role for the CH 4 yield. Indeed, similar results were previously demonstrated on Ta 3 N 5 and ZnSn­(OH) 6 . , Insight into the reaction reveals that the difference was that the CO 2 reduction occurred on the {100} facet and Pt 2+ -based cocatalyst for SrTiO 3 and x Pt 2+ -SrTiO 3 , respectively, as confirmed by the TEM and VB-XPS result. Hence, this confirmed that the different CO and CH 4 selectivity for the CO 2 reduction was dependent on the different surface chemistry with the present Pt 2+ species.…”
Section: Resultssupporting
confidence: 83%
“…Indeed, similar results were previously demonstrated on Ta 3 N 5 and ZnSn(OH) 6 . 29,30 Insight into the reaction reveals that the difference was that the CO 2 reduction occurred on the {100} facet and Pt 2+ -based cocatalyst for SrTiO 3 and xPt 2+ -SrTiO 3 , respectively, as confirmed by the TEM and VB-XPS result.…”
Section: Resultsmentioning
confidence: 89%
“…These results suggested that the NiSn(OH) 6 was promising for the CO 2 RR in natural air, despite the low CO 2 and H 2 O concentration. , E RHE = −1.9 V) was quilt difficult in thermodynamics [14]. The above results convinced the advantage of the NiSn(OH) 6 that is flexible and widely applicable for the CO 2 RR.…”
Section: Resultsmentioning
confidence: 66%
“…The surface metastable oxygen vacancies (V O ) are active sites playing strong interaction with the CO 2 or H 2 O molecule, thus accelerating the reaction rate by lowering the activation barriers [13,14]. As revealed, the V O could easily capture the CO 2 or H 2 O molecule by anchoring their oxygen atoms at the vacancy sites, and the V O -induced metal ions with unsaturated coordination (M δ+ ) could serve as the electron donor, thus weakening the corresponding oxygenbased bonding energy as a result of the molecule polarization [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%